A kind of thermal deformation rare earth permanent magnetic material and preparation method thereof

Through the preparation of thermal deformation iron boron magnet, the low -melting point auxiliary alloy has been spread to the inside of the main co -alloy magnetic powder, which reduces the thermal pressure and thermal deformation temperature, solves the problem of excessive grain grains, improved the magnetic stubborn stubbornness of the magnetic body. Power and preparation efficiency.

CN113936878BActive Publication Date: 2025-01-28GRIREM ADVANCED MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010608852.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-29
Publication Date
2025-01-28
Estimated Expiration
2040-06-29

AI Technical Summary

Technical Problem

During the preparation process of existing thermally deformed neodymium iron boron magnets, the thermal deformation temperature is high, resulting in excessive growth of grains, limiting the improvement of the material's magnetic properties.

Method used

By spreading the low -melting point auxiliary alloy to the inside of the main co -alloy magnetic powder, the crystal phase melting point of the main co -alloy magnetic powder and increasing the ratio of the crystal world are reduced, thereby reducing the thermal pressure and thermal deformation temperature to prevent the grains from growing.

Benefits of technology

Effectively reduce the temperature and thermal deformation temperature, prevent the grains from growing too much, improve the stubborn power of the magnet, and reduce the pressure and cost in the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113936878B_ABST
    Figure CN113936878B_ABST
Patent Text Reader

Abstract

The present invention relates to a thermal deformation rare earth permanent magnetic material and a preparation method thereof. The raw materials include a chemical formula of (R1 1‑c Ce c ) x Fe 100‑x‑y‑z M1 y B z The main alloy magnetic powder a and chemical formula are R2 in atomic percentage a (Cu 1‑b M2 b ) 100‑a Auxiliary alloy powder, wherein 0≤c≤1, 12≤x≤15, 0≤y≤10, 5≤z≤7, R1 is at least one of Nd, Pr, Dy, Tb, Ho, La, Gd, M1 is at least one of Si, Mn, Al, Co, Ga, Cu, 60≤a≤90, 0≤b≤1, R2 is at least one of Nd, Pr, La, Ce, M2 is at least one of Al, Zn, Ga, Sn, In. The material diffuses the low melting point auxiliary alloy into the main alloy powder, which not only reduces the melting point of the grain boundary phase of the main alloy magnetic powder, but also increases the proportion of the grain boundary phase, so that the hot pressing temperature can be reduced to below 650°C and the thermal deformation temperature can be reduced to below 700°C, thereby effectively preventing the growth of grains and improving the coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermally deformed rare earth permanent magnetic material and a preparation method thereof, belonging to the technical field of rare earth permanent magnetic materials. Background Art

[0002] Rare earth permanent magnet materials are permanent magnet materials based on intermetallic compounds formed by rare earth metal elements and transition metal elements. NdFeB permanent magnets are currently the most magnetic permanent magnet materials and are widely used in automobiles, air conditioners, wind power generation, national defense and aerospace, and are important functional materials supporting social progress.

[0003] At present, the preparation methods of fully dense NdFeB permanent magnets mainly include sintering and hot deformation. Compared with the sintering method, the hot deformation method has the advantages of low rare earth content, good corrosion resistance, and easy near-net forming. Hot-deformed NdFeB magnets are mainly composed of Nd2Fe14B main phase and grain boundary Nd-rich phase. The performance of hot-deformed magnets mainly depends on factors such as the intrinsic properties of the main phase, the shape and size of the grains, the c-axis orientation degree of the main phase grains, and the distribution of the grain boundary phase. The preparation process of hot-deformed magnets usually includes heating to compact the magnetic powder into an isotropic magnet, and reheating to hot-deform the isotropic magnet into an anisotropic magnet. During the hot deformation process, the deformation temperature should be higher than the melting point of the grain boundary phase. The grain boundary phase melted into a liquid state plays a role in lubrication and mass transfer during the deformation process. A suitable liquid phase is conducive to magnet deformation and grain orientation along the c-axis. However, in the existing technical solutions, the thermal deformation temperature is usually around 800°C, which is relatively high. Too high a thermal deformation temperature will cause excessive grain growth and limit the improvement of the magnetic properties of the material. Summary of the invention

[0004] The object of the present invention is to provide a thermally deformed rare earth permanent magnetic material, the raw materials of which include a chemical formula of (R1 1-c Ce c ) x Fe 100-x-y-z M1 y B z The main alloy magnetic powder a and chemical formula are R2 in atomic percentage a (Cu 1-b M2 b ) 100-aAuxiliary alloy powder, wherein 0≤c≤1, 12≤x≤15, 0≤y≤10, 5≤z≤7, R1 is at least one of Nd, Pr, Dy, Tb, Ho, La, Gd, M1 is at least one of Si, Mn, Al, Co, Ga, Cu, 60≤a≤90, 0≤b≤1, R2 is at least one of Nd, Pr, La, Ce, M2 is at least one of Al, Zn, Ga, Sn, In. The material diffuses the low melting point auxiliary alloy into the main alloy powder, which not only reduces the melting point of the grain boundary phase of the main alloy magnetic powder, but also increases the proportion of the grain boundary phase, so that the hot pressing temperature can be reduced to below 650°C and the thermal deformation temperature can be reduced to below 700°C, thereby effectively preventing the growth of grains and improving the coercive force.

[0005] Optionally, the mass of the auxiliary alloy powder does not exceed 10% of the mass of the main alloy magnetic powder a.

[0006] Optionally, the melting point of the auxiliary alloy powder is less than 500°C.

[0007] Optionally, the particle size of the main alloy magnetic powder a is 100 μm to 250 μm, and the particle size of the auxiliary alloy powder is 80 μm to 150 μm.

[0008] In the present application, the particle size refers to the median diameter of the powder.

[0009] Optionally, the thermally deformed rare earth permanent magnet material is composed of a matrix phase and a Cu-containing grain boundary rare earth-rich phase, the matrix phase grains are a nanoscale layered structure, the major axis / minor axis ratio of the layered structure is greater than 3, and the minor axis dimension is less than 100 nm.

[0010] Optionally, the matrix phase is (Ce, R1)2(Fe, Co) 14 B, wherein R1 is at least one of Nd, Pr, Dy, and Tb.

[0011] In a second aspect of the present application, a method for preparing the thermally deformed rare earth permanent magnetic material as described in any one of the above items is provided, comprising at least the following steps:

[0012] (1) providing a main alloy magnetic powder a and a supplementary alloy powder respectively;

[0013] (2) diffusing the auxiliary alloy powder into the main alloy magnetic powder a by heat treatment to obtain magnetic powder b;

[0014] (3) hot pressing the magnetic powder b to obtain a hot pressed magnet;

[0015] (4) thermally deforming the hot pressed magnet to obtain a thermally deformed rare earth permanent magnet material.

[0016] Optionally, the method for preparing the auxiliary alloy powder in step (1) comprises:

[0017] Weighing metal element raw materials according to the metal element ratio of the auxiliary alloy powder;

[0018] The weighed metal single substance raw material is melted into an alloy ingot, and then the alloy ingot is crushed into auxiliary alloy powder, which can be crushed by mechanical crushing and / or hydrogen crushing; or

[0019] Melting the weighed metal element raw material and directly atomizing it into auxiliary alloy powder; or

[0020] The weighed metal element raw material is melted, quenched into a strip, and then mechanically crushed into the required powder.

[0021] Optionally, the preparation method of the main alloy magnetic powder a in step (1) comprises:

[0022] Weigh the metal single substance raw materials according to the element ratio of the main alloy magnetic powder a;

[0023] The weighed metal single substance raw materials are melted into alloy ingots;

[0024] Melting the alloy ingot again and spraying it onto a rotating roller to prepare a strip;

[0025] The strip is prepared into main alloy magnetic powder a by mechanical crushing, wherein a single magnetic powder particle is composed of a plurality of crystal grains, and the crystal grain size is less than 50 nm.

[0026] Optionally, the mass of the auxiliary alloy powder does not exceed 10% of the mass of the main alloy magnetic powder a, preferably 1% to 5%.

[0027] Optionally, the melting point of the auxiliary alloy powder is less than 500°C.

[0028] Optionally, the particle size of the main alloy magnetic powder a is 100 μm to 250 μm, and the particle size of the auxiliary alloy powder is 80 μm to 150 μm.

[0029] Optionally, the thermally deformed rare earth permanent magnet material is composed of a matrix phase and a Cu-containing grain boundary rare earth-rich phase, the matrix phase grains are a nanoscale layered structure, the major axis / minor axis ratio of the layered structure is greater than 3, and the minor axis dimension is less than 100 nm.

[0030] Optionally, the matrix phase is (Ce, R1)2(Fe, Co) 14 B, wherein R1 is at least one of Nd, Pr, Dy, and Tb.

[0031] Optionally, the specific conditions of the heat treatment in step (2) include:

[0032] Carry out under vacuum or protective atmosphere conditions;

[0033] The heat treatment temperature is greater than the melting point of the auxiliary alloy powder and less than 600°C;

[0034] The heat treatment time is 0.5 to 5 hours.

[0035] Optionally, the heat treatment in step (2) is carried out in a heat treatment furnace that can rotate forward and reverse.

[0036] Optionally, the specific conditions for the hot pressing molding in step (3) include:

[0037] Carry out under vacuum or protective atmosphere conditions;

[0038] Hot pressing temperature is 550℃~650℃;

[0039] Hot pressing pressure is 80MPa~120MPa;

[0040] The hot pressing time is 1 to 30 minutes.

[0041] Optionally, the hot pressing process in step (3) is: placing the magnetic powder b obtained in step (2) into a hot pressing mold, heating the magnetic powder to a hot pressing temperature under vacuum or protective atmosphere, and applying hot pressing pressure to the magnetic powder to obtain a hot pressed magnet;

[0042] Optionally, the specific conditions of the thermal deformation described in step (4) include: the thermal deformation process described in step (4) is: placing the hot-pressed magnet in step (3) into a thermal deformation mold, heating the hot-pressed magnet to a thermal deformation temperature in a vacuum or protective atmosphere, and then applying thermal deformation pressure to the hot-pressed magnet so that the deformation of the magnet reaches 60% to 80%, thereby obtaining a thermally deformed magnet; wherein the thermal deformation temperature is 600°C to 700°C.

[0043] Beneficial effects:

[0044] First, since the low-melting-point alloy is diffused into the main alloy powder before hot pressing and hot deformation, the melting point of the grain boundary phase of the main alloy magnetic powder is lowered, and the proportion of the grain boundary phase is increased, so that the hot pressing temperature is reduced to below 650°C and the hot deformation temperature is reduced to below 700°C, which effectively prevents grain growth and improves coercive force.

[0045] Second, diffusion of the low-melting-point alloy is carried out before pressing, which is conducive to the uniform distribution of the low-melting-point alloy between the magnet grains. The grains are separated by grain boundaries, which significantly improves the magnetic isolation effect between the grains and is conducive to improving the coercive force.

[0046] Third, the main alloy magnetic powder contains Ce, which can reduce the melting point of the main phase, soften the main phase at a lower thermal deformation temperature, improve the deformation ability of the magnet, and cooperate with the low melting point grain boundary phase diffused to the grain boundary, which is conducive to the thermal deformation process and reduces the pressure required for thermal deformation. In addition, Ce is low in price and can also reduce material costs.

[0047] Fourthly, the size of the short axis direction of the thermally deformed magnet grains obtained in the present invention is less than 100 nm, and the major axis / minor axis ratio is greater than 3. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a transmission electron microscope image of the thermally deformed magnet prepared in Example 1.

[0049] Figure 2 This is a transmission electron microscope image of the thermally deformed magnet prepared in Comparative Example 1. DETAILED DESCRIPTION

[0050] The low-temperature thermal deformation rare earth permanent magnet and the preparation method thereof provided by the present invention will be further described below.

[0051] As analyzed in the background technology, the preparation of thermally deformed rare earth permanent magnets in the prior art has the problem of high thermal deformation temperature and high requirements on equipment. In order to solve this problem, the present invention provides a low-temperature thermally deformed rare earth permanent magnet material and a preparation method thereof.

[0052] The present invention provides a method for preparing a rare earth permanent magnet, which comprises the following steps:

[0053] S1, respectively providing a main alloy magnetic powder a and an auxiliary alloy powder;

[0054] S2, mixing the two powders in S1 and heat treating them in a vacuum or protective atmosphere to uniformly diffuse the auxiliary alloy powder into the main alloy magnetic powder a to obtain magnetic powder b;

[0055] S3, hot pressing the magnetic powder b under vacuum or protective atmosphere to obtain a hot pressed magnet;

[0056] S4, thermally deforming the hot pressed magnet under vacuum or protective atmosphere to obtain a thermally deformed magnet.

[0057] Wherein, the melting point of the auxiliary alloy powder in step S1 is less than 500°C. The melting point of the auxiliary alloy powder is lower than 500°C, which can obtain the following benefits: first, the auxiliary alloy powder can be diffused into the main alloy magnetic powder a at a lower temperature, and it is easy to diffuse evenly; second, diffusion at low temperature can prevent the grain growth of the main alloy magnetic powder a; third, the low melting point alloy is diffused into the main alloy magnetic powder, which can reduce the temperature of the hot pressing and hot deformation process, and at the same time can also play a role in reducing the hot pressing and hot deformation pressure to a certain extent, and reduce the requirements for equipment capacity.

[0058] Furthermore, the chemical formula of the auxiliary alloy powder in step S1 is R2 in atomic percentage. a (Cu 1-b M2 b ) 100-a , where 60≤a≤90, 0≤b≤0.8, R is one or more of Nd, Pr, La, Ce, and M2 is one or more of Al, Zn, Ga, Sn, and In. The use of light rare earth elements Nd, Pr, La, and Ce in the above-mentioned auxiliary alloy materials is beneficial to controlling the melting point of the alloy and reducing costs. A certain amount of Cu in the auxiliary alloy material will help improve the wettability between the alloy material and the main alloy magnetic powder grains. Adding one or more of the elements Al, Zn, Ga, Sn, and In can further adjust the melting point of the auxiliary alloy material and improve the wettability between the grain boundary phase and the main phase grains.

[0059] Furthermore, the preparation method of the auxiliary alloy powder in step S1 includes: smelting the ingredients into alloy ingots according to the element ratio of the auxiliary alloy, and preparing the required powder by mechanical crushing + hydrogen crushing, etc.; or directly atomizing the raw materials into the required powder after melting; or melting the raw materials, quenching them into strips, and then mechanically crushing them into the required powder.

[0060] The chemical formula of the main alloy magnetic powder a in step S1 is (R1 1-c Ce c ) x Fe 100-x-y-z M1 y B z , where 0≤c≤1, 12≤x≤15, 0≤y≤10, 5≤z≤7, R is one or more of Nd, Pr, Dy, Tb, Ho, La, Gd, and M1 is one or more of Si, Mn, Al, Co, Ga, and Cu. The main alloy powder provides magnetic properties for R2Fe 14 B tetragonal phase, the addition of Ce will make R2Fe 14The melting points of the B tetragonal phase and the grain boundary phase are lowered, which is conducive to hot pressing and hot deformation at lower temperatures. The Ce content c value should not be too low, otherwise the effect of lowering the melting point will not be obvious, but the Ce content should not be too high, otherwise it will reduce the intrinsic magnetic properties of the main phase and lead to reduced magnet performance. Therefore, 0.1≤c≤0.3 is preferred.

[0061] Furthermore, the preparation method of the main alloy magnetic powder a in step (1) is: smelting the alloy ingot according to the element ratio of the main alloy, melting the alloy ingot again and spraying it onto a rotating roller to prepare a strip, and preparing the strip into the required main alloy magnetic powder by mechanical crushing, wherein a single magnetic powder particle is composed of multiple grains, and the grain size is less than 50nm.

[0062] In order to allow the auxiliary alloy magnetic powder to fully diffuse into the main alloy magnetic powder a, further, in step (1), the particle size of the main alloy magnetic powder a is 100 μm to 250 μm, and the particle size of the auxiliary alloy powder is 80 μm to 150 μm.

[0063] The mass of the auxiliary alloy powder in step (2) does not exceed 10% of the mass of the main alloy magnetic powder a. Since the auxiliary alloy powder is non-magnetic, the amount added should not be too much, otherwise it will dilute the magnetism; if it is too little, the grain boundary phase ratio will be too small, and the effect of low-temperature thermal deformation will not be achieved. The amount of auxiliary alloy powder added is preferably 1% to 5% of the mass of the main alloy magnetic powder.

[0064] Furthermore, the heat treatment temperature in step (2) is above the melting point of the auxiliary alloy and below 600°C, and the heat treatment time is 0.5 to 5 hours. A heat treatment temperature above the melting point of the auxiliary alloy is conducive to the full melting and diffusion of the auxiliary alloy, but the diffusion temperature should not be too high, otherwise it is easy to cause the grain growth of the main alloy magnetic powder. Heat treatment below 600°C can prevent grain growth. Similarly, the heat treatment time should not be too short, otherwise the diffusion is insufficient, and too long will easily cause grain growth.

[0065] In order to ensure uniform diffusion, the heat treatment in step (2) is further carried out in a heat treatment furnace that can rotate forward and reversely.

[0066] The magnetic powder b processed by step S2 is composed of main phase grains with a size of less than 50nm and a low melting point grain boundary phase mixed with auxiliary alloy components. The grain boundary phase becomes a liquid phase during the hot pressing and hot deformation process, which plays the role of lubricating the grains, mass transfer, and promoting grain deformation and orientation. Therefore, the temperature and pressure in step S3 and step S4 can be adjusted according to the composition and proportion of the diffused auxiliary alloy.

[0067] The hot pressing process in step S3 is as follows: the magnetic powder b obtained in step S2 is placed in a hot pressing mold, the magnetic powder is heated to the hot pressing temperature under vacuum or protective atmosphere, and hot pressing pressure is applied to the magnetic powder to obtain a hot pressed magnet, wherein the hot pressing temperature is 550°C to 650°C, the hot pressing pressure is 80MPa to 120MPa, and the hot pressing time is 1 to 30 minutes. The purpose of hot pressing is to make the magnetic powder into a dense magnet, but the grains are not oriented during the hot pressing process. It is sufficient to select the lowest temperature and pressure possible while comprehensively ensuring the density and preparation efficiency of the magnet.

[0068] The thermal deformation process in step S4 is: placing the hot-pressed magnet in step S3 into a thermal deformation mold, heating the hot-pressed magnet to a thermal deformation temperature in a vacuum or protective atmosphere, and then applying a thermal deformation pressure to the hot-pressed magnet so that the deformation of the magnet reaches 60% to 80%, thereby obtaining a thermally deformed magnet, wherein the thermal deformation temperature is 600°C to 700°C, and the thermal deformation pressure is 30MPa to 60MPa.

[0069] The method provided by the present invention can reduce both the pressure and the temperature during hot pressing and thermal deformation. Compared with pressure, temperature is a more sensitive factor for grain growth, especially for nanocrystalline materials, and grain size is an important factor affecting the coercive force of rare earth permanent magnets. Hot deformation treatment at low temperature can effectively prevent excessive growth of magnet grains. The size of the short axis direction of the hot deformed magnet grains obtained in the present invention is less than 100nm, and the major axis / minor axis ratio is greater than 3.

[0070] Therefore, the present invention also provides a high coercive force nanocrystalline thermal deformation rare earth permanent magnet obtained by the above preparation method, which is composed of a matrix phase (Ce, R)2(Fe, Co) 14 B and a grain boundary rare earth-rich phase containing Cu, wherein R is one or more of the rare earth elements Nd, Pr, Dy, and Tb, and the matrix phase grains are nano-scale layered structures. The major axis / minor axis ratio of the layered nanocrystals is greater than 3, and the minor axis dimension is less than 100 nm.

[0071] In summary, the present invention adopts a low melting point alloy, and in the case of preventing the main alloy magnetic powder from growing up, the low melting point alloy is uniformly diffused into the main alloy powder before the hot pressing and hot deformation process, and a magnetic powder containing a certain proportion of low melting point grain boundary phase is obtained. At the same time, the main alloy magnetic powder contains a certain amount of Ce, which reduces the melting point of the main phase, so that the main phase can be softened at a lower hot deformation temperature, and the thermoplasticity of the magnet is enhanced, and the low melting point grain boundary phase diffused to the grain boundary works synergistically to reduce the hot pressing temperature to below 650°C and the thermal deformation temperature to below 700°C. When the thermal deformation temperature is below 700°C, the growth of grains during the thermal deformation process can be effectively prevented, and the size of the grains in the minor axis direction after thermal deformation can be controlled below 100nm. At the same time, because the magnet has good thermoplasticity, the major axis / minor axis ratio of the grains is greater than 3. This method is also beneficial in reducing the pressure during thermal deformation, which not only reduces the requirements for equipment, but also allows more grain boundary phases to be retained between the grains during thermal deformation without being squeezed out, thereby enhancing the magnetic isolation effect between the grains and increasing the coercive force of the magnet.

[0072] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0073] In the following examples, the magnetic properties (remanence B r 、Maximum magnetic energy product (BH) max and coercivity H cj ) was detected by vibrating sample magnetometer (VSM). The magnet grain size was observed and measured by transmission electron microscopy.

[0074] Example 1

[0075] The heat-deformed magnets were prepared according to the following steps:

[0076] 1) According to atomic percentage (Nd 0.9 Ce 0.1 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1340°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0077] 2) According to the atomic percentage Pr 68 Cu 32The ingredients are batched and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0078] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 2% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 530° C. and the heat preservation time is 1 hour. After cooling to room temperature in the furnace, magnetic powder b is obtained.

[0079] 4) The magnetic powder b was hot pressed for 3 min under vacuum conditions at a temperature of 600° C. and a pressure of 100 MPa to obtain a dense hot pressed magnet.

[0080] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 650° C. and a pressure of 50 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0081] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Tables 1 and Figure 1 .

[0082] Example 2

[0083] The heat-deformed magnets were prepared according to the following steps:

[0084] 1) According to atomic percentage (Nd 0.8 Ce 0.2 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1320°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0085] 2) According to the atomic percentage Pr 68 Cu 30Al2 component is prepared, and then induction smelting is used to melt the master alloy ingot. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into secondary alloy powder with a particle size of 80 microns to 150 microns.

[0086] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 1% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 570° C. and the heat preservation time is 0.5 hours. After cooling to room temperature in the furnace, magnetic powder b is obtained.

[0087] 4) The magnetic powder b was hot-pressed for 5 min under vacuum conditions at a temperature of 640° C. and a pressure of 100 MPa to obtain a dense hot-pressed magnet.

[0088] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 680° C. and a pressure of 60 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0089] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0090] Example 3

[0091] The heat-deformed magnets were prepared according to the following steps:

[0092] 1) According to atomic percentage (Nd 0.8 Ce 0.2 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1320°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0093] 2) According to the atomic percentage Pr 68 Cu 30The Ga2 component is prepared and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0094] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 2% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 550° C. and the heat preservation time is 1 hour. After cooling to room temperature with the furnace, magnetic powder b is obtained.

[0095] 4) The magnetic powder b was hot-pressed for 5 min under vacuum conditions at a temperature of 620° C. and a pressure of 100 MPa to obtain a dense hot-pressed magnet.

[0096] 5) The hot pressed magnet is subjected to heat deformation under vacuum environment at a temperature of 680° C. and a pressure of 50 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0097] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0098] Example 4

[0099] The heat-deformed magnets were prepared according to the following steps:

[0100] 1) According to atomic percentage (Nd 0.8 Ce 0.2 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1320°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0101] 2) According to the atomic percentage Pr 68 Cu 30The Ga2 component is prepared and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0102] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 5% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 550° C. and the heat preservation time is 2 hours. After cooling to room temperature in the furnace, magnetic powder b is obtained.

[0103] 4) The magnetic powder b was hot pressed for 8 min under vacuum conditions at a temperature of 620° C. and a pressure of 90 MPa to obtain a dense hot pressed magnet.

[0104] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 680° C. and a pressure of 45 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0105] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0106] Example 5

[0107] The heat-deformed magnets were prepared according to the following steps:

[0108] 1) According to atomic percentage (Nd 0.7 Ce 0.3 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 35m / s, the quenching temperature is 1300°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0109] 2) According to the atomic percentage Pr 68 Cu 30The Ga2 component is prepared and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0110] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 2% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 550° C. and the heat preservation time is 1 hour. After cooling to room temperature with the furnace, magnetic powder b is obtained.

[0111] 4) The magnetic powder b was hot pressed for 10 min under vacuum conditions at a temperature of 620° C. and a pressure of 100 MPa to obtain a dense hot-pressed magnet.

[0112] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 660° C. and a pressure of 45 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0113] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0114] Example 6

[0115] The heat-deformed magnets were prepared according to the following steps:

[0116] 1) According to atomic percentage Nd 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 30m / s, the quenching temperature is 1380°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0117] 2) According to the atomic percentage Pr 68 Cu 30The Ga2 component is prepared and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0118] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 2% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 550° C. and the heat preservation time is 1 hour. After cooling to room temperature with the furnace, magnetic powder b is obtained.

[0119] 4) The magnetic powder b was hot pressed for 10 min under vacuum conditions at a temperature of 620° C. and a pressure of 100 MPa to obtain a dense hot-pressed magnet.

[0120] 5) The hot pressed magnet is subjected to heat deformation under vacuum conditions at a temperature of 700° C. and a pressure of 55 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0121] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0122] Example 7

[0123] The heat-deformed magnets were prepared according to the following steps:

[0124] 1) According to atomic percentage (Nd 0.74 Pr 0.16 Ce 0.1 ) 13 Fe 76.9 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1340°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0125] 2) According to atomic percentage Nd 70 Cu 10 Zn20 The ingredients are batched and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 800℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into secondary alloy powder with a particle size of 80 microns to 150 microns.

[0126] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 3% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 580° C. and the heat preservation time is 2 hours. After cooling to room temperature in the furnace, magnetic powder b is obtained.

[0127] 4) The magnetic powder b was hot pressed for 15 min under vacuum conditions at a temperature of 650° C. and a pressure of 110 MPa to obtain a dense hot pressed magnet.

[0128] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 680° C. and a pressure of 60 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0129] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0130] Example 8

[0131] The heat-deformed magnets were prepared according to the following steps:

[0132] 1) According to atomic percentage Nd 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 30m / s, the quenching temperature is 1380°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0133] 2) According to the atomic percentage Pr 68 Cu 22 Zn 10The ingredients are batched and then melted into a master alloy ingot by induction melting. The molten master alloy is sprayed onto the surface of a water-cooled roller in an inert atmosphere to obtain a secondary alloy quenching strip, wherein the roller surface speed is 20m / s, the quenching temperature is 750℃, and the spraying pressure is 0.03MPa. The secondary alloy quenching strip is mechanically crushed into a secondary alloy powder with a particle size of 80 microns to 150 microns.

[0134] 3) The main alloy magnetic powder a and the auxiliary alloy powder are mixed evenly, wherein the auxiliary alloy powder accounts for 1% of the mass of the main alloy magnetic powder a. The mixed powder is placed in a vacuum heat treatment furnace with a rotatable furnace body for diffusion treatment, wherein the temperature is 580° C. and the heat preservation time is 2 hours. After cooling to room temperature in the furnace, magnetic powder b is obtained.

[0135] 4) The magnetic powder b was hot pressed for 30 minutes under vacuum conditions at a temperature of 650° C. and a pressure of 100 MPa to obtain a dense hot pressed magnet.

[0136] 5) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 680° C. and a pressure of 60 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0137] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0138] Comparative Example 1

[0139] The heat-deformed magnets were prepared according to the following steps:

[0140] 1) According to atomic percentage Nd 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 30m / s, the quenching temperature is 1380°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0141] 2) The main alloy magnetic powder a is hot pressed in a vacuum environment at a temperature of 675° C. and a pressure of 100 MPa to obtain a dense hot pressed magnet.

[0142] 3) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 730° C. and a pressure of 55 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0143] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Tables 1 and Figure 2 .

[0144] Comparative Example 2

[0145] The heat-deformed magnets were prepared according to the following steps:

[0146] 1) According to atomic percentage (Nd 0.8 Ce 0.2 ) 13.8 Fe 76.1 Co4Ga 0.5 B 5.6 The components are batched and then melted into a master alloy ingot by induction melting. The molten master alloy ingot is sprayed onto the surface of a rotating water-cooled roller in an argon atmosphere to obtain a quenching strip, wherein the roller surface speed is 33m / s, the quenching temperature is 1320°C, and the spraying pressure is 0.06MPa. The obtained quenching strip is mechanically crushed into a main alloy magnetic powder a with a particle size of 100 microns to 250 microns.

[0147] 2) The main alloy magnetic powder a is hot pressed in a vacuum environment at a temperature of 650° C. and a pressure of 90 MPa to obtain a dense hot pressed magnet.

[0148] 3) The hot pressed magnet is subjected to heat deformation under vacuum at a temperature of 720° C. and a pressure of 50 MPa, with a heat deformation amount of 70%, to obtain a heat deformed magnet.

[0149] The obtained hot deformed magnets were processed into samples of φ3mm×3mm and the magnetic properties were measured by VSM. The grain size was measured by transmission electron microscopy. The measured remanence (B r ), coercivity (H cj )、Maximum energy product (BH) max The grain size and major axis / minor axis size ratio of the magnet are shown in Table 1.

[0150] Table 1 Magnetic properties of thermally deformed magnets in various embodiments and comparative examples

[0151]

[0152]

[0153] It can be seen from Examples 1 to 8 in Table 1 that the preparation method provided by the present invention can effectively reduce the temperature of hot pressing and thermal deformation, prevent grain growth, and thus obtain a larger coercive force. It can be seen from the examples and comparative examples that the use of low melting point alloys diffused into the main alloy magnetic powder containing Ce has a significant synergistic effect of reducing the hot pressing and thermal deformation temperature and pressure.

[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thermally deformable rare earth permanent magnetic material, characterized in that: It consists of the matrix phase (Ce, R)2(Fe, Co) 14 B and a rare earth-rich phase containing Cu at the grain boundary, R is one or more of the rare earth elements Nd, Pr, Dy, Tb, and the raw materials include a chemical formula of (R1 1-c Ce c ) x Fe 100-x-y-z M1 y B z The main alloy magnetic powder a and chemical formula are R2 in atomic percentage a (Cu 1-b M2 b ) 100-a Auxiliary alloy powder, wherein 0≤c≤1, 12≤x≤15, 0≤y≤10, 5≤z≤7, R1 is at least one of Nd, Pr, Dy, Tb, Ho, La, and Gd, M1 is at least one of Si, Mn, Al, Co, Ga, and Cu, 60≤a≤90, 0≤b≤0.8, R2 is at least one of Nd, Pr, La, and Ce, and M2 is at least one of Al, Zn, Ga, Sn, and In; wherein the matrix phase grains are nanoscale layered structures, the major axis / minor axis ratio of the nanocrystals of the layered structure is greater than 3, and the dimension in the minor axis direction is less than 100 nm; the mass of the auxiliary alloy powder does not exceed 10% of the mass of the main alloy magnetic powder a, and the melting point of the auxiliary alloy powder is less than 500°C.

2. The material according to claim 1, characterized in that The particle size of the main alloy magnetic powder a is 100 μm to 250 μm, and the particle size of the auxiliary alloy powder is 80 μm to 150 μm.

3. The method for preparing the thermally deformed rare earth permanent magnetic material according to claim 1 or 2, characterized in that: At least the following steps are included: (1) providing a main alloy magnetic powder a and a supplementary alloy powder respectively; (2) diffusing the auxiliary alloy powder into the main alloy magnetic powder a by heat treatment to obtain magnetic powder b; (3) hot pressing the magnetic powder b to obtain a hot pressed magnet; (4) thermally deforming the hot pressed magnet to obtain a thermally deformed rare earth permanent magnet material.

4. The preparation method according to claim 3, characterized in that: The method for preparing the auxiliary alloy powder in step (1) comprises: Weighing metal element raw materials according to the metal element ratio of the auxiliary alloy powder; The weighed metal single substance raw material is melted into an alloy ingot, and then the alloy ingot is crushed into auxiliary alloy powder; or Melting the weighed metal element raw material and directly atomizing it into auxiliary alloy powder; or The weighed metal single substance raw material is melted, quenched into a strip, and then mechanically crushed into auxiliary alloy powder.

5. The preparation method according to claim 3, characterized in that: The preparation method of the main alloy magnetic powder a in step (1) comprises: Weigh the metal single substance raw materials according to the element ratio of the main alloy magnetic powder a; The weighed metal single substance raw materials are melted into alloy ingots; Melting the alloy ingot again and spraying it onto a rotating roller to prepare a strip; The strips are prepared into main alloy magnetic powder a by mechanical crushing.

6. The preparation method according to claim 3, characterized in that: The specific conditions of the heat treatment in step (2) include: Carry out under vacuum or protective atmosphere conditions; The heat treatment temperature is greater than the melting point of the auxiliary alloy powder and less than 600°C; The heat treatment time is 0.5 to 5 hours.

7. The preparation method according to claim 3, characterized in that: The specific conditions for the hot pressing molding in step (3) include: Carry out under vacuum or protective atmosphere conditions; Hot pressing temperature is 550℃~650℃; Hot pressing pressure is 80MPa~120MPa; The hot pressing time is 1 to 30 minutes.

8. The preparation method according to claim 3, characterized in that: The specific conditions of thermal deformation described in step (4) include: Carry out under vacuum or protective atmosphere conditions; Thermal deformation temperature is 600℃~700℃; Thermal deformation pressure is 30MPa~60MPa; The deformation is 60% to 80%.

Citation Information

Patent Citations

  • Mg-Cu grain boundary modified high-magnetism sintered Nd-Fe-B magnet and preparation process thereof

    CN103971875A

  • Nanocrystalline thermal deformation rare-earth permanent magnet with high coercivity and preparation method of nanocrystalline thermal deformation rare-earth permanent magnet

    CN105321646A